Exploring exotic nuclei: advancing the nuclear shell model beyond traditional magic numbers using the generalized interacting boson model - Krücken Cao Möller; Sachs Sherrill Porquet (Vertex, 2022)
The study of exotic nuclei and advancements in the nuclear shell model beyond traditional magic numbers have been at the forefront of nuclear physics research. This research aims to understand the nuclear structure and properties of exotic nuclei with extreme neutron-proton imbalances, going beyond the conventional understanding based on the well-established magic numbers. The theoretical framework of the Generalized Interacting Boson Model (GIBM) is employed to capture collective degrees of freedom and describe nuclear shapes and interactions more accurately. A numerical example of a hypothetical exotic nucleus with 8 protons and 20 neutrons is presented, showcasing the GIBM's ability to predict low-energy states and explore deviations from traditional magic numbers. The results demonstrate potential shell evolution and the interplay between spherical and deformed bosons in exotic nuclei. The implications of these findings for astrophysical processes, particularly in stellar nucleosynthesis, are discussed. The research opens new avenues for understanding the behavior of exotic nuclei and their relevance to the origin of elements in the universe. Collaborative efforts between experimentalists and theorists continue to shape this exciting frontier of nuclear physics, paving the way for deeper insights into the fundamental nature of matter